(untitled) (American Journal of Agricultural Science, Engineering, and Technology, 2021)
Frozen food is one of Bangladesh’s most valuable export items, comprising more than 80% of shrimp. The most cultivated area of shrimp is situated in the southern region of Bangladesh. This research was carried out to identify the core problem in the shrimp farming areas in order to support the related farmers in seeking a solution through the most common technology used by them. The study was conducted in Shyamnagar, Satkhira district with a total of 40 female respondents involved. This research showed that shrimp farming is pressurized by a lack of proper information on disease identification and its management. Mobile apps are considered the most common information providers among that community. The research defined the common problems and necessity through the system requirement specification (SRS) to provide needed details for the farmers that focused on mobile-app development eventually. It was found that disease (82.86%) and water quality (17.14%) are the most common issues while among the diseases White Spot Syndrome Virus and Yellow Head Virus Disease followed by Black Gill disease were the most alarming to handle without pre-management knowledge. The research also suggests developing voice-based mobile apps for shrimp farmers in the local language.